IZA Journal of European Labor Studies - Kahanec, Martin; de la Rica, Sara; Barrett, Alan
The IZA Journal of European Labor Studies publishes high-quality international research on a wide range of issues of relevance for European labor markets. In its scope it is policy-oriented and focused on applied research work. The Journal aims at contributing to the current policy debate across Europe and within its various countries. This includes analyses of European labor policy dealing with concrete policy problems, reforms, proposals or issues that are of concern for policy-making. In general, the IZA Journal of European Labor Studies publishes high-quality original research articles. Occasionally the journal also invites articles that are reviews or syntheses of the literature which have a clear policy relevance and which draw concrete policy conclusions. The IZA Journal of European Labor Studies belongs to the family of field journals in the IZA Journal Series with Springer, also including: (i) the IZA Journal of Labor Economics, (ii) the IZA Journal of Labor Policy, (iii) the IZA Journal of Migration, and (iv) the IZA Journal of Labor & Development. Each journal publishes 24 articles per year, where each article should be about 10,000 words (including tables, figures and references). This is a major joint product of the IZA network (and those who want to affiliate with IZA), which plays a central role in the evaluation process. It is an instrument for IZA to foster production of knowledge in the areas where IZA sees need. The aim of the new IZA Journal Series is to provide a high-quality, peer-reviewed outlet for papers, where the key characteristic of the submission procedure is the fast decision making and publication process. Acceptance/rejection decisions are expected to be made within one month; publication is expected within one month after submission of the final manuscript. The fast process from the submission to the acceptance/rejection decision is guaranteed by (i) an advanced desk rejection policy and (ii) the fact that only those papers refereed that require minor revisions are accepted while those not accepted are rejected without a detailed referee report. This requires the submission of manuscripts that are considered ready by the author(s) for direct publication if found suitable by the editorial team. The IZA Journals will be an online journal series accessible through SpringerOpen. This implies that electronic access to all five new journals is provided freely and permanently worldwide immediately upon publication.